2019
DOI: 10.1371/journal.pone.0212965
|View full text |Cite
|
Sign up to set email alerts
|

The first isolation of Clostridium difficile RT078/ST11 from pigs in China

Abstract: We investigated the molecular characteristics and antimicrobial susceptibility of Clostridium difficile isolated from animals in China. We obtained 538 rectal swabs from pigs, chickens and ducks in 5 provinces during 2015 and 2016. C . difficile isolates were characterized by detection of toxin genes, multilocus sequence typing and ribotyping. And antimicrobial susceptibility testing was performed using the agar dilution method. Out of 538 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
(56 reference statements)
5
15
0
Order By: Relevance
“…While these isolates showed high resistant rate to ERY (92.73%), followed by CLI (53.36) and CIP (27.2%). The C. difficile isolates from economic animals in our study showed relative high resistance rate to ERY than other countries (45.5-52.9%) [12,38]. In addition, the majority isolates resistant to ERY and CLI are RT126.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…While these isolates showed high resistant rate to ERY (92.73%), followed by CLI (53.36) and CIP (27.2%). The C. difficile isolates from economic animals in our study showed relative high resistance rate to ERY than other countries (45.5-52.9%) [12,38]. In addition, the majority isolates resistant to ERY and CLI are RT126.…”
Section: Discussionmentioning
confidence: 48%
“…However, such kind of study is quite limited in China, although there are many molecular studies of clinical C. difficile in China, even in the Asia-Pacific area [20,21]. Until now, there is only one report on C. difficile from pig, chicken and duck in China in 2019, but calf was not included [12]. Therefore, in this study, we determined to analyze the prevalence and genotypic characters of C. difficile from economic animals in China, including dairy calf, pig, sheep and chicken, which help to fully understand the situation of C. difficile from animals in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 3 ribotypes have been the sole or predominant strains identified in studies of livestock in North America, Europe, and Asia. 4,6,9,17,56,66,67,69,78,98,115,128,137,141,148 Yet, although ribotype 078 predominates, a wide range of strains can be identified, including other strains found in humans with CDI. 6,8,97 As in some other animal species, the ribotype distribution is different in Australia, where ribotype 078 is rare to nonexistent and various strains can be found, including some unusual strains such as ribotype 237.…”
Section: Pigsmentioning
confidence: 99%
“…Consequently, in the conducted study, confirmation was done by Vitek-2 compact system with including a particular positive control reference strain of C. difficile (ATCC 9689) in each experiment. Other studies used Api 20A ( Kouassi et al, 2014 ), API Rapid ID 32A ( Troiano et al, 2015 ) or molecular ( Bakri, 2018 ; Romano et al, 2018 ; Zhang et al, 2019 ; Usui et al, 2020 ) tests to confirm C. difficile isolates.…”
Section: Discussionmentioning
confidence: 99%